Diary of a wimpy kid (No brainer) - Kinney, Jeff (Michigan: Puffin books, 2023)
When the town threatens to close the crumbling middle school, Greg realizes this means he is going to be sent to a different school than his best friend, Rowley Jefferson, and considers saving the building
Keywords: Diary of a wimpy kid, English, Fiction